Titanium(IV) Derivatives of N-(o-Hydroxy Substituted Benzyl) Alanines - Shah, Ranjana; Aman, Robina; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several titanium(IV) derivatives of N-(o-hydroxy substituted benzyl) alanines have been prepared by the interaction of titanium tetraisopropoxide with the latter in 1 : 1, 1 : 2, 1 : 3, 1 : 4 and 2 : 3 molar ratios in benzene medium. The various compounds thus prepared were generally obtained as coloured solids and amongst them those containing isopropoxy group(s) were found to be hygroscopic. All these compounds were characterized by azeotrope and elemental analyses, as well by IR and PMR spectral measurements.